ANALISIS WEBISTE E-TILANG DI KEJAKSAAN NEGERI KOTA BATU - Maulina Putri, Devita; Rosyadi, Hudan Eka; Cahyani, Sofia (Universitas Islam Balitar, 2023)
The E-ticket website is an E-government innovation by the Indonesian government that aims to help people pay ticket fines, avoid extortion, and increase accountability, transparency and fairness. The Attorney General's Office for Batu, East Java Province, has implemented this innovation, but the results have not been optimal. This is due to a lack of Human Resources from the community as users and the lack of socialization about the importance of implementing E-tickets. This study aims to find out how E-government can be implemented at the Batu State Prosecutor's Office in East Java Province through the E-tilang website. In addition, it will also identify factors that support and hinder the implementation of E-government. This analysis uses the successful elements of e-government development according to the Harvard JFK School of Government, namely Support, Capacity, and Value. The research method used is descriptive qualitative, with data collection techniques through observation, interviews and documentation. Based on the results of the study, the Support variable is good, because support, allocation of human resources, and outreach have been carried out by the Batu State Prosecutor's Office. Variable Capacity is also sufficient, with available financial resources and technological infrastructure. However, the Value variable is not yet optimal, due to the low level of public participation as well as technical problems and features for refunding overpaid fines on the E-ticket website which are not yet available. This has become an obstacle in the implementation of E-government through E-tickets at the Batu State Prosecutor's Office, East Java Province.